PENTINGNYA MANAJEMEN PENGEMBANGAN SUMBERDAYA MANUSIA DALAM LINGKUNGAN MULTIBUDAYA - Suminta Simatupang (Smart Education, 2026)
Abstract: A multicultural environment is a social environment that has diversity and coexists with differences, but often this creates challenges in the process of adjustment. This article aims to provide students and readers with an understanding of human resource development management in a multicultural environment as an effort to facilitate adaptation and thinking in dealing with the cultural diversity of each employee in an organization. This research uses a literature review and uses descriptive analysis methods. Human resource development management (HRD) is carried out through education and training both formally and informally. There are five important domains in human resource development management, namely professionalism, competitiveness, functional competence, participatory excellence and cooperation. Human resource development management in these five important domains will be implemented if implemented with good and correct management control so that the goals of the organization will be realized and able to create quality human resources and be able to face all differences that exist in the work environment. Keywords: Management, Human Resources, Multicultural Environment Abstrak: Lingkungan multibudaya merupakan lingkungan sosial yang memiliki keberagaman dan hidup berdampingan dengan perbedaan, tetapi tidak jarang hal ini menimbulkan tantangan dalam proses penyesuaian diri. Artikel ini bertujuan memberikan pemahaman kepada mahasiswa dan pembaca mengenai managemen pengembangan sumber daya manusia dalam lingkungan multibudaya sebagai upaya untuk memfasilitasi adaptasi dan pemikiran dalam menghadapi keberagaman budaya yang dimiliki setiap karyawan dalam suatu organisasi. Penelitian ini menggunakan kajian literatur dan menggunakan metode analisis deskriptif. Managemen pengembangan sumber daya manusia (SDM) dilakukan melalui pendidikan dan pelatihan baik secara formal maupun informal. Terdapat lima domain penting dalam managemen pengembangan sumber daya manusia yaitu profesionalitas, daya kompetitif, kompetensi fungsional, keunggulan partisipatif dan kerja sama. Managemen pengembangan sumber daya manusia pada kelima domain penting tersebut akan terlaksana apabila dilaksanakan dengan kontrol managemen yang baik dan benar sehingga tujuan dari organisasi akan terwujud dan mampu menciptakan sumber daya manusia yang berkualitas dan mampu menghadapi segala perbedaan yang ada dalam linkungan kerja. Kata Kunci: Managemen, Sumberdaya Manusia, Lingkungan Multibudaya